Halogen‐Bonded Assemblies of Arylene Imides and Diimides: Insight from Electronic, Structural, and Computational Studies. Issue 46 (20th July 2020) - Mandal, Kalyanashis; Bansal, Deepak; Kumar, Yogendra; Rustam,; Shukla, Jyoti; Mukhopadhyay, Pritam
Abstract: Halogen‐bonding interactions in electron‐deficient π scaffolds have largely been underexplored. Herein, the halogen‐bonding properties of arylene imide/diimide‐based electron‐deficient scaffolds were studied. The influence of scaffold size, from small (phthalimide) to moderately sized (pyromellitic diimide or naphthalenediimides) to large (perylenediimide), axial‐group modification, and number of halo substituents on the halogen bonding and its self‐assembly was probed in a set of nine compounds. The structural modification leads to tunable optical and redox properties. The first reduction potential E 1 / 2 1 ranges between −1.09 and −0.17 V (vs. SCE). Two of the compounds, that is, 6 and 9, have deep‐lying LUMOs with values reaching −4.2 eV. Single crystals of all nine systems were obtained, which showed Br⋅⋅⋅ O, Br⋅⋅⋅ Br, or Br⋅⋅⋅ π halogen‐bonding interactions, and a few systems are capable of forming all three types. These interactions lead to halogen‐bonded rings (up to 12‐membered), which propagate to form stacked 1D, 2D, or corrugated sheets. A few outliers were also identified, for example, molecules that prefer C−H⋅⋅⋅ O hydrogen bonding over halogen bonding, or noncentrosymmetric rather than centrosymmetric organization. Computational studies based on Atoms in Molecules and Natural Bond Orbital analysis provided further insight into the halogen‐bonding interactions. This study can lead to a predictive design tool‐box to further explore related systems on surfaces reinforced by these weak directional forces. Abstract : Halogen‐bond‐based self‐assembly : The halogen‐bonding properties of arylene imide/diimide‐based electron‐deficient π scaffolds were explored. The influence of scaffold size, axial groups, number of halogen atoms, and imide carbonyl O versus S atoms on the halogen bonding and its self‐assembly was probed in a set of nine compounds. Single‐crystal XRD, AIM analysis, and NBO analysis provided insight into these interactions.